2003
DOI: 10.5194/aab-46-143-2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth traits of eight beef cattle breeds in the Czech Republic

Abstract: Abstract. Eight beef cattle breeds, Angus (A), Blonde d' Aquitaine (BA), Charolais (C), Czech Pied (CP), Hereford (H), Limousin (L), Piemontese (P) and Simmental (S), were analysed for the following calf traits: birth weight (BW), 210- and 365-day weight ( 210W, 365W) and average daily gains from birth to 210 days (ADG1), from 210 to 365 days (ADG2) and from birth to 365 days (ADG3). Phenotypic parameters were estimated by linear model procedures including the fixed effects of year of birth (1992–1998), herd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
20
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 2 publications
9
20
3
3
Order By: Relevance
“…These findings were in agreement with results reported by Dymnicki et al (1996) and Dadi et al (2002). Similarly, Jakubec et al (2003) reported high weights and average daily gains for Blonde d'Aquitaine, Charolais and BS calves that were higher in comparison with calves raised in Slovakia (except for birth weights). Říha et al (2001) found out the highest beef traits for Charolais calves.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings were in agreement with results reported by Dymnicki et al (1996) and Dadi et al (2002). Similarly, Jakubec et al (2003) reported high weights and average daily gains for Blonde d'Aquitaine, Charolais and BS calves that were higher in comparison with calves raised in Slovakia (except for birth weights). Říha et al (2001) found out the highest beef traits for Charolais calves.…”
Section: Discussionsupporting
confidence: 83%
“…Goyache et al (2003) reported the highest weaning weight for calves descending from 7-11 years old cows (calving 5-9). This is in agreement with findings of Říha et al (1999) and Jakubec et al (2003). Except for birth weight, Přibyl et al (2003) reported highest weights and fastest growth for calves of 5-7 years old dams.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Piemontese and Limousin breeds had been evaluated for crossing on Friesian dairy cows in several European countries (MCGUIRK et al, 1998;JACUBEC et al, 2003). In majority of these studies, Piemontese progeny out of Friesian cows had a higher growth rate than Limousin (HRÛSKA 1993;GRUNDY et al, 2000).…”
Section: Introductionmentioning
confidence: 99%